Airlines: Standardize Your International Advertising!. (May 2023) - Décaudin, Jean-Marc; Lacoste, Denis
The aim of this article is to determine whether it is appropriate to standardize airline communication at the international level. Most previous research on international services advertising has carried out content analyses only, without measuring effectiveness. The contribution of this article lies in measuring the effectiveness of advertising strategies in an international service sector. The reaction of consumers to specific advertisements in France and the United Kingdom (UK) was measured. A sample of 200 consumers from these two countries were exposed to various airline advertising campaigns representing the five main advertising strategies presented in the literature. The effectiveness of each advertising strategy was measured. The results show that there are no major differences in the effectiveness of the different advertising strategies in France and the UK. These findings seem to indicate that when airlines are present in the two countries, they should standardize their advertising communication.